Hidup Irit Bukan Hidup Pelit: Edukasi Literasi Keuangan dan Pemanfaatan Kebutuhan Primer di Panti Jompo Salomo Agape - Dading Damas Ario Wicaksono; Florencia Irena Lawita; Juniati Gunawan; Murtanto Murtanto; Natasha Richelle Valencia Ibrahim (LPMP Imperium, 2026)
Financial literacy is an essential competency for older adults in managing resources wisely, particularly due to limited income and dependence on external assistance. This Community Service Program (PKM) aimed to enhance the understanding of residents at the Salomo Agape Nursing Home regarding the concept of living frugally without being stingy through simple financial literacy education and the efficient utilization of primary needs. The program employed a non-formal, humanistic, and participatory approach through sharing sessions, interactive discussions, and edutainment activities such as painting and singing. Evaluation was conducted verbally through contextual question and answer sessions and participatory observation. The results demonstrated that all indicators of participants’ understanding were categorized as very good (above 80%), with the highest achievement found in the aspect of strategies to avoid financial problems (93%). Participants were able to distinguish between being frugal and being stingy, as well as understand the importance of prioritizing primary needs. In addition to improving cognitive aspects, the program also positively influenced affective aspects, including greater openness, self-confidence, and awareness in utilizing assistance responsibly. Therefore, a financial literacy program based on a participatory approach is effective for older adults and should be implemented continuously to support their well being and independence.